STRATEGI PENGEMBANGAN KOTA MAGELANG SEBAGAI KAWASAN ANDALAN DI PROVINSI JAWA TENGAH - Nuraini, Rica Ayu; Setiartiti, Lilies (Universitas Muhammadiyah Yogyakarta, 2017)
This research aims to determine the classification of economics structure and the leading sectors of Magelang. The analysis of the research employs Klassen’s Tipology, Location Quotient and SWOT. The results show that the city of Magelang is included in the advanced and fast-growing regions with high economic growth and high per capita income. Location Quotient (LQ) shows all secondary and tertiary sectors are included in the leading sectors, while agricultural sector, mining sector and manufacturing sector are not included in the leading sector. Based on SWOT analysis, there are leading sectors that needs to be improved to persuade the better economic condition in the main area of Magelang city, by taking action some possible development strategies, such as, improving the base sector’s products by utilizing advanced technology, maximizing the realization of investment and maximizing the sale of leading sector products as well as creative industry products. Another possible startegies are creating a conducive business environment and improving the competitiveness of the regional economy.